The Prospect of Applying CAMA System for rating Valuation in Malaysia - Daud, Dzurllkanian @ Zulkarnain
Traditionally in Malaysia, the valuation of properties can conceivably be conducted using four methods including Cost method, Comparison method, Residual method, and Profit method. Of all these methods, the comparison method is the most common approach used by the appraisals. As per Local Authorities Act 1976 (Act 171), all properties are required to be valued every five years. The revaluation or valuation of the property has been carried out by manual approach. This process is very tedious, time consuming and cost effective. It also requires more manpowers and maintaining manual records is a difficult task. In practice, most of appraisals in Malaysia are using conventional system for the valuation of a property. However the countries like United Kingdom, Australia, U.S, Africa, New Zealand and Europe were systemised with the use of CAMA (i.e. computerized system) to reduce the labour cost and time. Therefore, this CAMA system is very much essential to the appraisals at local authorities in Malaysia due to the increase in quantity of properties. The technique applied in CAMA is a quantitative approach called the multiple regression analysis for analysing market data to produce a set of models for valuation purposes. Now this system is particularly used in different states of Malaysia especially in Johor and Pahang. Also GIS system is incorporated with CAMA system to identify the location of the properties. This CAMA-GIS system, developed using a combination of softwares (statistical packages, database and GIS), is menu-driven and user-friendly. The system is developed in different stages. The initial stage involves a study on the data requirement for appraisal purposes. The aim is to identify the possible variables influencing the values for model building. Once the set of determinant variables is established, the database is then designed by incorporating basic information of property such as property ownership, land area, lot number, and account number needed for the purpose of property tax administration. Moreover the analysis of user requirements and needs are carried out to provide information for the database and user-interface designs. Once completed, the system accomplishes the primary objective of arriving at the value of properties that are reliable, accurate, equitable and defensible. The system can also display the geographical information thus improves the administration of property tax.